The Effect of Visitor Number on the Behavior of Zoo-Housed Macropods. (4th July 2021) - Meade, Jessica; Melfi, Vicky A.; Keith, Melanie; Burns, Alicia L.
ABSTRACT: Free-range exhibits are used by zoos to allow visitors to experience or interact with animals in a semi-natural setting; close interactions with animals have been shown to increase empathy and contribute to conservation outcomes, and as such zoos are increasingly implementing free-range style exhibits to facilitate this goal. We aimed to investigate whether this close proximity to zoo visitors impacted upon four species of macropod (red kangaroo Macropus rufus, red-necked wallaby Macropus rufogriseus, swamp wallaby Wallabia bicolor, and quokka Setonix brachyurus ) in a free-range exhibit in an Australian zoo. Specifically, we used instantaneous scan sampling to assess animal behavior and examined whether visitor number affected the proportion of individuals that exhibited four target behaviors; visitor-directed vigilance, retreat, resting, and foraging behavior. We found that the proportion of individuals exhibiting visitor-directed vigilance significantly increased as pedestrian visitor number increased for three of the four species, and the proportion of individuals that were resting was significantly negatively related to visitor number for both wallaby species. The proportion of individuals of each species foraging or retreating was unrelated to visitor number. These data suggest that a visitor effect exists in a walk-through exhibit of macropods, and once visitor numbers go beyond a threshold, the behavior of more animals is impacted, likely compromising welfare. Interestingly, quokka do not appear to be affected by zoo visitors; which may be due to visitor pressure being perceived differently due to evolutionary differences, or that housing and husbandry ameliorate the visitor effect for this species but not others. Like many studies before, taking a species-specific approach to understanding zoo visitor–animal interactions has determined how the visitor effect likely impacts macropods differently.